MAIN AGE-RELATED CUTANEOUS CHANGES IN MEN GROUNDED ON THE RESULTS OF ULTRASONIC DIAGNOSTICS - Reznichenko, N.Yu.; Dyudyun, A.D. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the ultrasonic characteristics of skin and blood flow in men of different age groups. 120 men aged from 25 to 64 years were examined. The reduction in thickness of the different layers of the skin in men of older age groups was fixed. Low levels of flow velocity (its maximum and average figures), as well as high resistance index and pulse activity index, were fixed in males of mature age. In cases when antioxidants, nootropics and angioprotectors were prescribed for prophylaxis, flow velocity (its maximum and average figures) increased in skin vessels, resistance index and pulse activity index dеcreased. It was shown that the use of antioxidants, nootropics and angioprotectors was effective for the prevention of skin aging and blood-flow violations in it in males of older age groups.
Keywords: aging; skin; blood flow; men